Effect of total hepatectomy and administration of branched-chain amino acids on regional norepinephrine, dopamine, and amino acids in rat brain. - Herlin, P M (1983)
In rats after total hepatectomy, the effect of infusing glucose alone or combined with branched-chain amino acids on amino acid concentrations in plasma and cerebral cortex and on catecholamine levels in eight different regions of the brain was studied. Infusion of branched-chain amino acids reduced the accumulation of tryptophan, phenylalanine, and tyrosine in plasma, while in cerebral cortex, the concentrations of phenylalanine and tyrosine were normalized and that of tryptophan was reduced greatly. In rats with hepatectomy and glucose infusion alone, norepinephrine levels were decreased in seven of eight brain regions with the exception of striatum, while dopamine was reduced significantly in striatum only. Infusion of branched-chain amino acids resulted in higher norepinephrine in cortex, mesencephalon, and hypothalamus and higher striatal dopamine 18 hours after hepatectomy. Thus, infusing branched-chain amino acids and reducing the accumulation of various neutral amino acids in brain may partially prevent the loss of norepinephrine from brain after total hepatectomy.